1994
DOI: 10.2960/j.v16.a6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Age and Growth of Northern Shrimp (Pandalus borealis) in Davis Strait (NAFO Subareas 0+1) Using Cluster and Modal Analyses

Abstract: Shrimp (Pandalus borealis) length frequency distributions obtained during research surveys in Davis Strait (NAFO Subareas 0+1) from 1983 to 1987 were analyzed for age and growth. Samples were combined within year on the basis of their similarity using cluster analysis. Modal analyses were performed for males only, separating the distribution mixtures into normal components which were interpreted as ages 1 to 6, inclusive. Mean carapace lengths at these ages were estimated at 8.4, 12.3, 15.7, 18.5, 20.6 and 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, length frequencies given in Kanneworff and Wieland (2002) would suggest that sex change occurred on average at age 5-6, which is 1 year later than described by Horsted and Smidt (1956) and 1 year earlier than estimated by Savard et al (1994).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, length frequencies given in Kanneworff and Wieland (2002) would suggest that sex change occurred on average at age 5-6, which is 1 year later than described by Horsted and Smidt (1956) and 1 year earlier than estimated by Savard et al (1994).…”
Section: Discussionmentioning
confidence: 72%
“…Northern shrimp (Pandalus borealis) is a protandric hermaphrodite with a circumpolar distribution in the northern hemisphere (Shumway et al, 1985;Bergstrøm, 2000), changing to the female stage at carapace lengths (CLs) between 18 and 26 mm after being 4-7 years as a male in West Greenland waters (Horsted and Smidt, 1956;Savard et al, 1994). Charnov and Anderson (1989) proposed that local populations of pandalid shrimp have neither a fixed size nor age at sex transition, and sex allocation theory of Charnov (1982) predicts that pandalid shrimp decrease size at sex change during periods of low female abundance to compensate for a decreased reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Based on samples from the Davis Strait, Savard et al (1994) provided estimates of minimum, maximum and mean lengths at age, cf. Table 2.…”
Section: Data and Materialsmentioning
confidence: 99%
“…Based on samples from the Davis Strait, Savard et al (MS 1989) provided estimates of mean lengthat-age (Table 1). Carlsson and Kanneworff (MS 1993) found that these estimates are still consistent with estimates based on data from the present stock.…”
Section: Methodsmentioning
confidence: 99%